Online Survey Design and Development: A Janus-Faced Approach. (July 2013) - Lauer, Claire; McLeod, Michael; Blythe, Stuart
In this article we propose a Janus-faced approach to survey design—an approach that encourages researchers to consider how they can design and implement surveys more effectively using the latest web and database tools. Specifically, this approach encourages researchers to look two ways at once; attending to both the survey interface (client side; what users see) and the database design (server side; what researchers collect) so that researchers can pursue the most dynamic and layered data collection possible while ensuring greater participation and completion rates from respondents. We illustrate the potentials of a Janus-faced approach using a successfully designed and implemented nationwide survey on the writing lives of professional writing alumni. We offer up a series of questions that a researcher will want to consider during each stage of survey development.